The midwifery of God: tokological deliverance in 1 Timothy 2:15 in light of early Jewish and Christian readings of Genesis 3:16 - Gathergood, Emily J. (2022)
This study seeks to elucidate the enigmatic promise that woman “will be saved through childbearing” (σωθήσεται διὰ τῆς τεκνογονίας) in 1 Timothy 2:15. The idea is notoriously difficult to interpret within existing conceptions of Pauline soteriology due to its distinctively gendered horizon. What is the relationship between salvation and childbearing? Is the soteriology of 1 Timothy gender-differentiated? The central thesis is that being saved διὰ τῆς τεκνογονίας is about the divine preservation of women’s bodies during childbirth. “Tokological deliverance” from the pain and danger to life normally associated with childbearing is, however, part of a wider soteriological scheme which culminates in the eschatological salvation of body and soul.